Blinkenberg et Høybye: Dictionnaire Danois-Français, 4e édition. København: Nyt Nordisk Forlag Arnold Busck, 1991 - Andersen, Bjarne Kjeldberg (HERMES - Journal of Language and Communication in Business, 1993)
No abstract.